2020
DOI: 10.1155/2020/8818242
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Deformation and Acoustic Emission Characteristics of Arch Roadway under Different Unloading Rates

Abstract: The essence of roadway excavation is a process of unloading at the periphery, and the influence of unloading paths on surrounding rock damage is directly related to the selection of support design and construction technology. The real stress state of surrounding rock is often affected by different excavation conditions in the actual construction process. Therefore, a testing system of excavation and unloading model was developed to simulate the unloading process of the arch roadway under different excavation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Figure 2 shows the axial stress-time curve of coal and rock. After a full investigation and under the condition that the simulation results are not false, this paper selects the commonly used slow unloading confining pressure rate of 0.03 MPa/s and confining pressure value of 3 MPa [38,39]. e three-axis loading and unloading of composite coal are divided into five stages: 0-2 s is a three-dimensional stress loading stage.…”
Section: Stress Field Analysismentioning
confidence: 99%
“…Figure 2 shows the axial stress-time curve of coal and rock. After a full investigation and under the condition that the simulation results are not false, this paper selects the commonly used slow unloading confining pressure rate of 0.03 MPa/s and confining pressure value of 3 MPa [38,39]. e three-axis loading and unloading of composite coal are divided into five stages: 0-2 s is a three-dimensional stress loading stage.…”
Section: Stress Field Analysismentioning
confidence: 99%
“…(4) Under the simulation conditions in steps ( 1) and ( 2), triaxial loading is carried out again. When the stress reaches 80% of the peak intensity recorded in step (3), under the condition of ensuring that the simulation results are not distorted, three commonly used slow unloading confining pressure rates of 0.003 MPa/s, 0.03 MPa/s, and 0.05 MPa/s [43,44] are selected for unloading simulation until the composite coal and rock rupture, and the simulation ends. In order to better study the relationship between the unloading fracture mechanics stage of coal-rock and its infrared radiation temperature, the stress change process must first be clarified.…”
Section: Simulation Model Of Composite Coal-rock Unloadingmentioning
confidence: 99%
“…Based on scanning electron microscopy (SEM), Hu et al [17] identified microcracks in the surrounding rock and obtained the fracture characteristics of granite. Dresen et al [18][19][20][21] used the monitoring, statistics, and positioning functions of acoustic emission (AE) signals to study the evolution law of microscopic failure characteristics and achieved good results. In addition, many scholars [22][23][24][25][26] studied the damage and failure characteristics of the surrounding rock by combining model tests and numerical simulation methods.…”
Section: Introductionmentioning
confidence: 99%